Gelora politik Kelantan - Abdul Halim Mahmood, 1945- (Kuala Lumpur : Tinta Enterprise, 1992)
Political power games in Kelantan.
In Malay.
Other title on cover: UMNO vs. PAS + S46, BERJASA terkubur.
Keywords: Kelantan -- Politics and government